A Long-Term Study of Collection Use Based on Detailed Library of Congress Classification, a Statistical Tool for Collection Management Decisions. Issue 3 (2nd July 2016) - Hughes, Michael
ABSTRACT: This article presents the results of a long-term study of the use of print monographs in a non-circulating fine arts library spanning a period of seven academic years, from September 2008 through June 2015. The data were collected daily across the entire collection and are analyzed using Library of Congress Classification subclasses. Changes in subject areas of use over time are highlighted. The usefulness of this type of collection analysis to collection managers is discussed, and examples of how the findings are being used at the author's library are presented.